Visitors’ Willingness to Pay (WTP) at Kionsom Recreation Centre, Inanam, Kota Kinabalu, Sabah - Andy Russel Mojiol; Ziyad Zamri; Muhammad Azrul Hilmi; Maskir Gitom (e-VIBS, Faculty of Science and Natural Resources, 2017)
Aim of this study is to determine the willingness to pay (WTP) of visitors to pay admission fees for conservation at Kionsom Recreation Centre (KRC) and opinion on ecosystem services of KRC. Contingent Valuation Method (CVM) of WTP is used to find out the respondent’s payment valuation on study areas by using open-ended payment vehicle. 140 of questionnaire is distributed in the area using convenience sampling but only 100 questionnaires are selected as they are fully answered by the respondents. Result showed that factor of WTP influenced by gender, age and distance between respondent’s place to Kionsom Recreational Centre. A regression model was created and the results shows that gender, age and distance have relationship on the amount of WTP that stated by respondents. Mean maximum WTP by per visitor to KRC is RM 2.89. Besides, most of the respondents valued highly the services of tree and ecosystem services of the site. The visitors also agrees that conservation fee collected are suitable for development purposes and add more recreation activities to attract visitor to visit Kionsom Recreational Centre (KRC). Future study on differences payment vehicle and elicitation method of contingent valuation on the site is highly recommended.